«Великий кордон» Ф. Дж. Тернера та Запоріжжя - Пилипенко, В. (Сiверянський лiтопис, 2015)
Розвідка присвячена теорії Великого кордону та застосуванню її для пояснення
історії України. Здійснено порівняння «класичного» американського фронтиру та
Запоріжжя. Як головну особливість українського Великого кордону автор називає
його статичність. Статья посвящена концепции фронтира (границы) и использованию ее для
объяснения истории Украины. Автор сравнивает «классический» американский
фронтир и Запорожье. Главной особенностью и отличием Запорожья определяется его статичность. The article is dedicated to the Frontier Thesis and the opportunities of its usage for the history
of Ukraine explanation. F.Turner’s ideas about the history of the USA are been compared
with ideas about Ukrainian variant of the Frontier – Zaporizhzha. The initiative of American
frontier colonization belonged to the state and was financed by the state. On the contrary,
Zaporizhzha was colonized spontaneously. The state didn’t participate in the process. Author
considers huge assimilation process to be the peculiarity of Ukrainian Frontier, because all
immigrants on Cossacks’ lands had to make a conversion to Orthodoxy. The Cossacks always
proclaimed their faith to Ukrainian people. American Frontier was integrated to the state
gradually and turned into region dominating in the politics. However, Zaporizhzha always
stayed beyond political borders.
The main peculiarity of Ukrainian Frontier is distinguished as static. American Frontier
was always moving to the West, though the Ukrainian one didn’t have such territory as the
lands in front were populated by the Tatars.